Unusual case of malignant pleural mesothelioma - Rajaratnam, Timothy Johanan (BMJ Case Rep, 2021)
We present the case of a 65-year-old woman who presented with progressive dysphagia and was diagnosed with achalasia. She subsequently developed bilateral chylous pleural effusions, with no cause identified despite extensive investigations (including computed tomography (CT) scans, gastroscopy and medical thoracoscopy (MT)) and review at a dedicated pleural multidisciplinary team meeting. Despite optimal supportive management she deteriorated and was admitted to the intensive care unit, where she passed away due to sepsis and respiratory failure 10 months after initial presentation. A postmortem returned a diagnosis of epithelioid mesothelioma, encasing the carina, distal oesophagus and coeliac axis. Mesothelioma only very rarely presents with either chylous effusions or achalasia. Additionally while MT normally conveys excellent sensitivity for pleural malignancy, it was insufficient here. This case highlights how an unusually located mesothelioma can produce an unusual clinical picture. It also suggests a role for early video-assisted thoracoscopy to aid diagnosis.